1996
DOI: 10.2503/jjshs.65.297
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Arbuscular Mycorrhizal Fungus Inoculation on Growth of Apple (Malus ssp.) Seedlings.

Abstract: The means of enhancing the growth of seedlings of apples, Malus pumila Mill. var. domestica Schneid. (cv. McIntosh, American Summer Pearmain, Jonathan, Golden Delicious, Starking Delicious, Fuji, Mutsu and Red Gold) and Malus sieboldii Rehd., through inoculation of arbuscular mycorrhizal (AM) fungus [Glomus etunicatum (GE) and Gigaspora margarita (GM)] were investigated. Eight weeks after inoculation, AM fungus infection occurred in all combinations of apple cultivars and fungus species. The rate of AM fungus-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 13 publications
0
4
0
2
Order By: Relevance
“…They found that mycorrhizal frequency in the roots of apple trees in organic orchards was higher (48.8%), and lower in the roots of trees growing in orchards managed by conventional methods (43.7%). Matsubara et al (1996) inoculated Malus pumila Mill. var.…”
Section: Discussionmentioning
confidence: 99%
“…They found that mycorrhizal frequency in the roots of apple trees in organic orchards was higher (48.8%), and lower in the roots of trees growing in orchards managed by conventional methods (43.7%). Matsubara et al (1996) inoculated Malus pumila Mill. var.…”
Section: Discussionmentioning
confidence: 99%
“…BBP2TP Ambon (2012) melaporkan bahwa diinokulasi mikoriza di daerah perakaran dapat mempercepat pertumbuhan bibit kakao. Hal ini sejalan dengan pernyataan Matsubara et al (1996) bahwa tanaman yang terinfeksi mikoriza memiliki tinggi tanaman, diameter batang, bobot kering akar dan tajuk, konsentrasi P pada bagian akar maupun tajuk lebih tinggi dibandingkan dengan tanpa mikoriza.…”
Section: Pemanfaatan Mikroorganisme Penambat Nitrogenunclassified
“…Initial work provides evidence that inoculation of young apple trees with AMF may reduce incidence of the fungal pathogens Dematophora necatrix and Botryosphaeria sp. ( Raj and Sharma, 2009 ; Krishna et al, 2010 ) and improve seedling growth rates and nutritional status ( Miller et al, 1985 ; An et al, 1993 ; Matsubara et al, 1996 ; Forge et al, 2001 ); however, these studies are of limited relevance to apple growers due to their short duration and as commercial apple trees are never grown from seedlings, but propagated clonally as grafted rootstocks and scions. Indeed, the extent to which interactions between the rootstock and scion, and their genetic identities, determines the magnitude of AMF induced benefits is almost entirely unknown ( Albacete et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%